2021
DOI: 10.1016/j.virusres.2020.198215
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 gp41 genetic diversity and enfuvirtide resistance-associated mutations among enfuvirtide-naïve patients in southern China

Abstract: Background: Human immunode ciency virus (HIV) increasing molecular diversity and emergence of drug resistant mutants remain a major concern in Southern China, enfuvirtide (ENF/T-20) is the rst entry inhibitor used in patients failing highly active antiretroviral therapy (HAART). However, data on HIV-1 gp41genetic diversity and primary ENF resistance-associated mutations among treatment-naïve patients in southern China is limited. The objective was to identify molecular diversity and ENF resistance patterns of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…HIVDR or mutations to PIs and other antiretroviral drugs (ARV) were also emerging. Yang et al investigated the prevalence of integrase strand transfer inhibitors (INSTI)-associated resistance of HIV-1 strains in Henan Province during 2018-2020 (40). The prevalence of INSTI resistance was 1.2% overall, 0.63% for ART-naive patients, 2.05% for ART-treated patients with 14.63% for INSTI-treated and 0.76% for INSTI-naive patients.…”
Section: Hiv Drug Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…HIVDR or mutations to PIs and other antiretroviral drugs (ARV) were also emerging. Yang et al investigated the prevalence of integrase strand transfer inhibitors (INSTI)-associated resistance of HIV-1 strains in Henan Province during 2018-2020 (40). The prevalence of INSTI resistance was 1.2% overall, 0.63% for ART-naive patients, 2.05% for ART-treated patients with 14.63% for INSTI-treated and 0.76% for INSTI-naive patients.…”
Section: Hiv Drug Resistancementioning
confidence: 99%
“…The prevalence of INSTI resistance was 1.2% overall, 0.63% for ART-naive patients, 2.05% for ART-treated patients with 14.63% for INSTI-treated and 0.76% for INSTI-naive patients. In a study of HIV-1 gp41 genetic diversity and enfuvirtide (ENF/T-20) drug resistance-associated mutations (DRMs) among enfuvirtide-naive patients in southern China, known DRMs were detected in 27.5% of ENF treatment-naive patients, which have been proved to elevate resistance to ENF ( 41 ). Undoubtedly, HIVDR or DRMs will continue to evolve in an increasing trend which warrants enhanced surveillance and monitoring.…”
Section: Molecular Epidemiologymentioning
confidence: 99%
“…Thus, no natural major resistance mutations to T-20 were observed. The L44M change found in group P consensus sequence, previously associated with 1.8-fold resistance to T-20 in vitro (Mink et al, 2005), was previously found in T-20 naïve subjects from China (Chang et al, 2021), maybe reflecting a resistance transmission during primoinfection. New HIV-1 fusion inhibitors are under development (Luque and Camarasa, 2021) and previous studies showed that optimized T-20 derivates could have been effective inhibitors of infection for multiple HIV-1 variants (Chen et al, 2019).…”
Section: Discussionmentioning
confidence: 52%
“…The major polymorphisms were R46K/M/Q, E137K, and S138A. R46K/M/Q and S138A were predominant in subtype CRF07_BC, and E137K was prevalent in subtype B [ 121 ].…”
Section: Entry Inhibitor Drugs Resistancementioning
confidence: 99%